Ethical Considerations in Research on Virtual Reality Games — A Systematic Literature Review - Vale, Lucas Medeiros de Araújo; Petry, Arlete dos Santos (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This systematic literature review aimed to investigate how ethics has been addressed in studies on virtual reality (VR) games. The goal was to contribute to a deeper understanding of the ethical implications of these games and provide insights for establishing guidelines that promote more responsible practices in the field. The research was conducted between February and March 2025 in the Scopus, IEEE Xplore, SpringerLink, and ACM Digital Library databases, using terms related to ethics and VR game development. After screening, six studies were included. The qualitative analysis followed Saldaña’s Coding Cycles method, using network creation in Atlas.TI to identify and categorize the main ethical challenges, developers’ responsibilities, and necessary guidelines for ethical practices in VR game development. The results indicate that the literature still lacks a systematic incorporation of ethics, highlighting the need for clearer regulations, robust guidelines, and greater awareness of the psychological and social impacts of these experiences.